A Leadership Solution to Workplace Stress - Monica L. Rousseau (University of North Florida, 2011)
Sources of stress can be found nearly everywhere: in school, at home, in traffic, and maybe most importantly -in the workplace. Chronic workplace stress, also known as "burnout", has been linked with both psychological and physiological illnesses. As most Americans spend about halfoftheir waking hours at work, the workplace is an excellent location to evaluate specific risk factors and implement stress reducing programs. Although a number ofsuch programs are currently in practice, the majority ofthem only offer techniques and coping mechanisms to individuals already exhibiting some, or several, ofthe many severe symptoms ofchronic stress. The purpose ofthis paper is to propose a new upstream solution to workplace stress by implementing the 1985 Bennis and Nanus model of leadership into the managerial practices within businesses. In addition to reducing employee mal-health, healthcare costs, and lost time due to illnesses, the model could solidify and contribute to the prestige, and growth of the public health education profession.